VKORC1 mutations in rodent populations of a tropical city-state as an indicator of anticoagulant rodenticide resistance - Cliff Chua; Mahathir Humaidi; Erica Sena Neves; Diyar Mailepessov; Lee Ching Ng; Joel Aik (Scientific Reports, 2022)
Abstract Anticoagulant rodenticides are commonly used in rodent control because they are economical and have great deployment versatility. However, rodents with Single Nucleotide Polymorphism (SNP) mutations within the Vkorc1 gene are resistant to the effects of anticoagulant rodenticide use and this influences the effectiveness of control strategies that rely on such rodenticides. This study examined the prevalence of rat SNP mutations in Singapore to inform the effectiveness of anticoagulant rodenticide use. A total of 130 rat tail samples, comprising 83 Rattus norvegicus (63.8%) and 47 Rattus rattus complex (36.2%) were conveniently sampled from November 2016 to December 2019 from urban settings and sequenced at exon 3 of Vkorc1. Sequencing analysis revealed 4 synonymous and 1 non-synonymous mutations in Rattus rattus complex samples. A novel synonymous mutation of L108L was identified and not previously reported in other studies. Non-synonymous SNPs were not detected in the notable codons of 120, 128 and 139 in R. norvegicus, where these regions are internationally recognised to be associated with resistance from prior studies. Our findings suggest that the prevalence of anticoagulant rodenticide resistance in Singapore is low. Continued monitoring of rodenticide resistance is important for informing rodent control strategies aimed at reducing rodent-borne disease transmission.